KANDUNGAN ZAT HARA FOSFAT PADA MUSIM BARAT DAN MUSIM TIMUR DI TELUK HURUN LAMPUNG - Santoso, Arif Dwi (Jurnal Teknologi Lingkungan, 2007)
The result of phosphate analysis in Hurun Bay Lampung described thatconcentration phosphate in the West season was greater than in the East season. In the February 2003, phosphate concentration was 9.51±1.54 ì g/L while in July 2003 around 6.32±3.8 ì g/L. The phosphate dissociation and phosphate run-off from land through river may increase phosphate concentration in West season. The other result shows that phosphate concentration in the surface was higher than in the bottom layer in the all season.